The Architecture of Zakat Institutions in Indonesia: A SWOT Analysis - Rozaan, Rofiq Achmad; Ibadurahman, Daud; Kurniawan, Riko; Pimada, Laila Masruro (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
Indonesia, as the country with the largest Muslim population in the world, certainly has a zakat system managed by the Amil Zakat Agency (BAZNAS) and the Amil Zakat Institution (LAZ) which is regulated in Law Number 23 of 2011 concerning Zakat Management. In practice, the management of zakat has not been carried out properly because there are still many people who pay zakat, not through amil institutions but directly hand it over to the community. So, zakat funds collected in institutions are not optimal and have an impact on the gaps that arise between the potential and the realization of zakat. This study aims to determine the management of zakat institutions in Indonesia and educate the public to pay zakat through institutions. This research is qualitative with a literature review model based on SWOT analysis. In the results of the analysis, it was found that there is a need for an appropriate strategy to correct deficiencies and fend off threats that exist in zakat institutions. These strategies include: (1) increasing the professionalism of zakat management through increasing incentives both material and non-material, then providing training and amil certification in collaboration with BNSP; (2) adapting information technology for efficient and effective governance as a means of transparency of zakat institutions and; (3) encouraging the literacy level of zakat awareness to the public by outreach, creating interesting educational content about zakat fiqh and collaborating with Islamic boarding schools and schools to form a zakat curriculum.